2004
DOI: 10.1023/b:myco.0000038436.51918.d9
|View full text |Cite
|
Sign up to set email alerts
|

Candiduria in Hospital Patients: A Study Prospective

Abstract: The presence of Candida species in the urine is frequent among hospitalized patients. We studied sample urine of 205 hospitalized patients during a 1-year period to determine the incidence of nosocomial candiduria. The yeasts were isolated in 22% (45/205) urine cultures and risk factors in these patients were analyzed. Candida albicans was isolated in 35.6% and C. tropicalis (22%) was the second most frequent species isolated. Most patients were women (57.8%) with a mean age of 48.7 years. The principal risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
52
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 13 publications
14
52
5
1
Order By: Relevance
“…This study showed that in most cases of candiduria the patient had a urinary catheter (92.6%). Similar results have been obtained by Kobayashi et al (2004), who verified that 84.4% of the patients with candiduria had a catheter. According to Klotz and Smith (1990), yeasts are able to adhere to the catheter, allowing colonization in this device.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that in most cases of candiduria the patient had a urinary catheter (92.6%). Similar results have been obtained by Kobayashi et al (2004), who verified that 84.4% of the patients with candiduria had a catheter. According to Klotz and Smith (1990), yeasts are able to adhere to the catheter, allowing colonization in this device.…”
Section: Discussionsupporting
confidence: 88%
“…These data are in accordance with other Brazilian studies [42][43][44][45] . In our study the frequency of UTI/1,000 urinary catheter (UC) days was greater than in studies realized in developing countries 46 , and although these infections are responsible for almost 40% of all NI, they continue to be unrepresentative in Brazilian hospitals, considering that the majority of them (80%) are associated with the use of urinary catheters 47,48 .…”
supporting
confidence: 93%
“…The principal risk factors include antibiotic therapy, urinary catheterization, surgical procedures, female sex and extended hospitalization. 3 Moreover, multiple site colonization with Candida species is also being commonly recognized as a major risk factor for invasive fungal infections in critically ill patients. 4 There is paucity of data from India on fungal infections in the critical care setting with variable results.…”
Section: Original Articlementioning
confidence: 99%